1982
DOI: 10.1093/clinchem/28.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay for pregnancy-associated plasma protein A.

Abstract: A specific and highly sensitive radioimmunoassay for determination of pregnancy-associated plasma protein A in human serum is described. The minimum detection limit for this protein was 2.9 micrograms/L. The within- and between-assay coefficients of variation were 4.0 and 4.5%, respectively. The circulating protein was detected within 32 days of conception in eight normal pregnancies and within 21 days in a twin pregnancy. Circulating concentrations in the mother at term were consistently higher (10-fold) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
1

Year Published

1983
1983
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…On the other hand, Bischof et al (19826) found no difference in plasma PAPP-A concentration between the follicular and the luteal phase. The results of these studies from Geneva and Aberdeen are in sharp contrast with those done in Sydney where Sinosich et al (1984) were unable to demonstrate any PAPP-A at all in the blood of non-pregnant women either in the proliferative or the luteal phase, or before 28 days after ovulation in the case of a pregnancy (Sinosich et al 1982). The aim of this study was to clarify these controversial results and to investigate the pattern of serum PAPP-A in women with normal menstrual cycles in more detail.…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…On the other hand, Bischof et al (19826) found no difference in plasma PAPP-A concentration between the follicular and the luteal phase. The results of these studies from Geneva and Aberdeen are in sharp contrast with those done in Sydney where Sinosich et al (1984) were unable to demonstrate any PAPP-A at all in the blood of non-pregnant women either in the proliferative or the luteal phase, or before 28 days after ovulation in the case of a pregnancy (Sinosich et al 1982). The aim of this study was to clarify these controversial results and to investigate the pattern of serum PAPP-A in women with normal menstrual cycles in more detail.…”
contrasting
confidence: 77%
“…Concomitantly with the development of more sensitive radioimmunoassays for PAPP-A (Bischof et a/. 1981a;Sinosich et al 1982;Anthony et al 1983) PAPP-A was discovered in the blood of non-pregnant women before (Bischof et al 1981b) and after the menopause (Bischof et al 1982~). In our laboratory an enzyme immunoassay for PAPP-A was developed (Bersinger 1983) and we were able to confirm the presence of PAPP-A in the serum of non-pregnant women using this alternative technique.…”
mentioning
confidence: 99%
“…Standards were the second international reference preparation (IRP) 75/537 of intact hCG; the detection limit was 5 IU/l. Serum PAPP-A levels were measured by radioimmunoassay as described by Sinosich et al (1982). The control samples were used to determine the median values for each week; all data were expressed as multiples of these medians (MOM).…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen affected and 66 unaffected pregnancies with samples stored at 9-14 weeks' gestation were available for study. Samples were retrieved from storage and measured for PAPP-A at the Royal London Hospital by radio-immunoassay described in detail previously (Sinosich et al, 1982). Figure I shows the individual PAPP-A concentration for each pregnancy according to gestational age.…”
mentioning
confidence: 99%